Proton pump inhibitor use as a risk factor for Enterobacteriaceal infection: a case–control study. Issue 1 (September 2018) - Cunningham, R.; Jones, L.; Enki, D.G.; Tischhauser, R.
Summary: Background: Gastric acid suppressants increase the risk of gastroenteritis by allowing ingested pathogens to survive passage through the stomach. It is not known whether the same mechanism affects transmission of Enterobacteriaceae. A case–control study was undertaken to answer this question. Aim: To determine whether use of proton pump inhibitors (PPIs) increases the risk of infection with Enterobacteriaceae in hospital patients. Methods: Retrospective case–control study in a teaching hospital in South West England. Cases were 126 patients infected with extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae between April 2014 and March 2015. Use of PPIs, H2 receptor antagonists or antacids at the time of admission or in the preceding six months was compared with 126 demographically matched controls infected with non-ESBL-producing Enterobacteriaceae and 126 uninfected controls, matched by primary diagnosis. Findings: Sixty-six of 126 ESBL cases, 62 of 126 non-ESBL controls and 34 of 126 uninfected controls were prescribed PPIs on or within six months of admission. Multi-variable logistic regression analysis gave an odds ratio of 3.37 [95% confidence interval (CI) 1.84–6.18] for PPI exposure vs uninfected controls and 1.15 (95% CI 0.68–1.95) for ESBL infection vs non-ESBL infection. H2 receptor antagonists and antacids were not significantly associated with infection. Conclusion: PPI exposure within the previous six months is significantly associated with infection with both ESBL- and non-ESBL-producing bacteria. Reducing inappropriate use of PPIs may be a novel way to reduce transmission, which might reduce antibiotic use and help control antimicrobial resistance.